Handbook of research on investigations in artificial life research and development - Habib, Maki K., 1955- (Hershey, PA : IGI Global, Engineering Science Reference, 2018)
'This book provides a forum on the study of living systems, human level artificial systems, and machines that exhibit intelligent autonomous behavioral characteristics. It promotes research in emerging disciplines of artificial life to improve and comprehend real-world problems. This book explores all concepts, theories, systems, and procedures that exhibit properties, phenomena, or abilities of any living system'--
Includes bibliographical references.
Keywords: Intelligent personal assistants (Computer software).; Automatic machinery; Artificial intelligence; Artificial life